Front Cover. Issue 4 (11th November 2020) - Unknown
Abstract : Cutaneous vasculature and skin structure is involved in many skin conditions and diseases which renders non‐invasive examination techniques imperative. In this review, various optical imaging and spectroscopic approaches are briefly discussed for dermatological applications. For each optical system, the configurations, advantages, limitations and specific dermatological applications on humans are addressed. Further details can be found in the article by Amalina Binte Ebrahim Attia, Renzhe Bi, Kapil Dev, Yao Du, and Malini Olivo (e202000010 ). Abstract : Cutaneous vasculature and skin structure is involved in many skin conditions and diseases which renders non‐invasive examination techniques imperative. In this review, various optical imaging and spectroscopic approaches are briefly discussed for dermatological applications. For each optical system, the configurations, advantages, limitations and specific dermatological applications on humans are addressed. Further details can be found in the article by Amalina Binte Ebrahim Attia, Renzhe Bi, Kapil Dev, Yao Du, and Malini Olivo (e202000010 ).